Gender Equality in the Qur’an: A Thematic and Critical Interpretation of Women-Related Verses - Rahmat Hamid; Halimah Basri; Achmad Abu Bakar; Muhammad Ismail; Anisah Alamshah; Andi Adil Shafwan Shafwan (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2025)
Gender inequality in some Muslim societies is often legitimized by narrow interpretations of religious texts. This study investigates the concept of gender equality in the Qur’an through a thematic-critical analysis of verses concerning women. Employing a qualitative library research method, it integrates tafsīr maudhu‘ī (thematic exegesis) with critical hermeneutics. Primary sources include the Qur’an and authentic hadiths, while secondary sources consist of classical and contemporary tafsir literature, along with feminist interpretations by scholars such as Amina Wadud and Asma Barlas. The findings indicate that the Qur’an affirms gender equality in terms of spiritual dignity, moral responsibility, and human potential. However, the historical development of tafsir has often been shaped by patriarchal contexts, leading to gender-biased interpretations. This study outlines a progression from literalist to more contextual hermeneutical approaches, highlighting the Qur’an’s interpretive flexibility in addressing evolving social realities. The study concludes that recovering the Qur’an’s original message of justice and equality necessitates a contextual and inclusive interpretive framework. By reaffirming the equal status of men and women as moral agents and servants of God, it contributes to contemporary discussions on gender justice in Islam.